1997
DOI: 10.1002/(sici)1096-9861(19970210)378:2<283::aid-cne10>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of GABAergic and glycinergic premotor neurons projecting to the facial and hypoglossal nuclei in the rat

Abstract: The distribution of inhibitory premotor neurons for the facial and hypoglossal nuclei was examined in the lower brainstem of the rat. A retrograde axonal tracing method with the fluorescent tracer, tetramethylrhodamine dextran amine (TMR-DA), was combined with immunofluorescence histochemistry for glutamic acid decarboxylase (GAD), i.e., the enzyme involved in gamma-aminobutyric acid synthesis, or glycine. In the rats injected with TMR-DA unilaterally into the facial or hypoglossal nucleus, the distribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(82 citation statements)
references
References 66 publications
4
78
0
Order By: Relevance
“…Neurons containing inhibitory amino acids have been found in the hypoglossal nucleus (Takasu et al, 1987;Aldes et al, 1988) and spinal ventral horn (Shupliakov et al, 1993). On the other hand, immunohistochemistry combined with retrograde tracer injection technique revealed that GABAergic and glycinergic neurons in the nucleus gigantocellularis ␣ and ventralis in the rat, which corresponds to the nucleus magnocellularis (NMC) in the cat, project to the spinal ventral horn (Holstege, 1991;Holstege and Bongers, 1991;Ellenberger, 1999) and hypoglossal nucleus (Li et al, 1997). GABAergic neurons in the PIA are reported to project to the hypoglossal nucleus (Li et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurons containing inhibitory amino acids have been found in the hypoglossal nucleus (Takasu et al, 1987;Aldes et al, 1988) and spinal ventral horn (Shupliakov et al, 1993). On the other hand, immunohistochemistry combined with retrograde tracer injection technique revealed that GABAergic and glycinergic neurons in the nucleus gigantocellularis ␣ and ventralis in the rat, which corresponds to the nucleus magnocellularis (NMC) in the cat, project to the spinal ventral horn (Holstege, 1991;Holstege and Bongers, 1991;Ellenberger, 1999) and hypoglossal nucleus (Li et al, 1997). GABAergic neurons in the PIA are reported to project to the hypoglossal nucleus (Li et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, immunohistochemistry combined with retrograde tracer injection technique revealed that GABAergic and glycinergic neurons in the nucleus gigantocellularis ␣ and ventralis in the rat, which corresponds to the nucleus magnocellularis (NMC) in the cat, project to the spinal ventral horn (Holstege, 1991;Holstege and Bongers, 1991;Ellenberger, 1999) and hypoglossal nucleus (Li et al, 1997). GABAergic neurons in the PIA are reported to project to the hypoglossal nucleus (Li et al, 1997). Although inhibitory amino acid containing neurons are found in the PIA (Rampon et al, 1996;Maloney et al, 2000), the neuronal type projecting to the spinal cord from this region (Kuypers and Maisky, 1975;Tohyama et al, 1979;Matsuyama et al, 1999) remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…4Q). Inhibitory interneurons that contact the facial motoneurons have been reported (Li et al 1997). An additional tonic input that is required to bias the motoneurons that are driven by inhibitory input could be provided by serotonergic projections (Dolphin and Greengard 1981;McCall and Aghajanian 1979).…”
Section: Candidate Models For a Whisking Central Pattern Generatormentioning
confidence: 99%
“…Thus hypoglossal premotor neurons are ventrolateral and dorsolateral in the medullary reticular formation (122,297,1263), and the majority of trigeminal and facial premotor neurons are in the pontomedullary and parvicellular reticular formations (482,535,850,1263). Some of these premotor neurons are GABAergic, glycinergic, or glutamatergic (738,739,1210,1277,1278). In addition to these regions, a smaller number of premotor neurons to trigeminal, facial, and hypoglossal nuclei are located in 1) pontine nuclei (Kölliker-Fuse; parabrachial nucleus; and trigeminal, facial, and hypoglossal nuclei); 2) periaqueductal gray of the midbrain (facial and hypoglossal nuclei); 3) periambigual region (hypoglossal and facial nuclei); 4) vestibular nuclei (facial nucleus); 5) gigantocellular reticular nucleus (all 3 nuclei); and 6) paralemniscal zone in the lateral midbrain and external cuneate nucleus (facial nucleus) (175, 297, 474, 482, 544, 737-739, 935, 1209, 1263, 1404).…”
Section: B Afferent Projections To Orofacial Motor Nucleimentioning
confidence: 99%